Brazil - Early Child Development : A Focus on the Impact of Preschools - World Bank (Washington, DC, 2013)
The report focuses on preschool, as an effective early childhood development (ECD) intervention, especially for improving the status of the poorest groups in Brazil's population. Because of data limitations, the focus is primarily on pre-schooling, with some discussions on day care, and other services for the younger age group (0-3 years). Although the country is now out of the economic recession of the late 1990s, and, has laid the basis for an economic growth free of inflation, nonetheless, substantial development imbalances still need to be addressed. This will require sustained economic growth, and a range of policy interventions that affect the broad structure of the economy, therefore, this study looks at the impact of ECD, particularly preschool, in redressing these distortions. The main structural dimensions of access to pre-schooling are higher enrollments among older children, showing that enrollments - eight percent in the 0-3 age group - were seen to be particularly low in comparison with industrialized nations, though similar to other Latin American countries; that enrollments are lower in the mid-west, south, and north of the country in comparison to the northeast, and southeast, with the largest rural-urban disparities in the mid-west, and southeast; and, that the richest ten percent of the population account for fifty six percent of access to preschool, while only twenty four percent of the poorest forty percent, attend these services. Findings suggest a strengthened preschool financing, improved access to the poorest, and combined preschool services with other ECD services.